Avaliação do desempenho mecânico de protótipo executado com blocos EVA: estudo de impactos horizontais em alvenarias e suas interações com outros elementos da construção. - Lima Filho, Marçal Rosas Florentino (2008)
The utilization of residues of the footwear s industry, especially E.V.A. residues(Ethilene Vinil Acetate) in the Civil Construction Industry has been the focus of the researches. It is known that such residues can be used as artificial aggregates instead of natural aggregates in the production of lightweight cement composites. The focus of this research is the mechanical conduct of EVA blocks (normal dimensions) isolated and applied in prisms and masonries. The EVA block was also evaluated in real scale in LABEME and compared with a soil-cement prototype and theoretical results. Tests of horizontal impacts and interactions between masonries and others elements of the building( abrupt shutting door tests and suspended pieces effects in walls) took place. Based on the results, the conclusion is that it is possible to propose blocks with 60% of EVA aggregate, substituting natural aggregates in volume, having a minimum resistance to compression over or equal 1,0 MPa (in Laboratory molding), that are confirmed compatible with the non-structural function. Thus, it s believed that the perspectives for the viability of the utilization of this residue in the manufacture of blocks for civil construction are very good. This will certainly contribute for a double reduction of negative impacts in the environment, as long as it offers an alternative destiny to such residues and a consummation reduction of natural resources (sand and hail), promoting the sustainable development for the activity of civil construction.